Dose-dependent efficacy of antioxidant nanoparticles on red blood cells storage - Saeid Barzegar; Mohammad Reza Rezvani; Majid Safa; Amir Amani; Alireza Abbaspour; Aliakbar Pourfathollah; Javad Hashemi; Farhad Zaker (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Transfusion of healthy red blood cells (RBCs) after storage is important. One of the storage lesions on blood bags is oxidative stress. One way to prevent increased oxidative stress is to use antioxidant nanoparticles (NPs). Superoxide dismutase (SOD) and catalase (CAT) play an important role in antioxidant defense on RBC. poly lactic-co-glycolic acid (PLGA) is a nontoxic biodegradable polymer that is approved by the Food and Drug Administration for drug delivery. This study aimed to assess dose-dependent efficacy of SOD-CAT-polyethylene glycol -PLGA on RBCs storage. MATERIALS AND METHODS: Using a descriptive study, during 1 month, twenty donors from Bojnourd Blood Donation Center were selected. NPs with different concentrations were injected into the satellite bags after directing blood to them. On target days, experiments were performed on the samples taken. Electrospray was employed to prepare SOD-CAT-PLGA NPs. Twenty packed RBCs were isolated from the whole blood bags by the mechanical method, and certain amount of product was transferred to the satellite bags. On days 1, 7, 14, 21, 28, and 35, bags were sampled. Malondialdehyde (MDA), prooxidant-antioxidant balance (PAB), and Annexin V were performed on the samples taken. The repeated measures analysis with the help of SPSS software version 20 was performed on samples. RESULTS: MDA increased in both groups. The maximum increase in test group was seen in concentration 12 mg (MDA Day 14, test [1.93 ± 0.3], [P MDA < 0.001]). Maximum increase in PAB was seen in concentration 12 mg (from 444 ± 1.7 to 563 ± 2.5) (P PAB = 0.000). Furthermore, PS expression increased in the concentration of 12 mg greater than other concentration in consecutive (from 5.00 ± 0.8 to 22.26 ± 1.7, [P < 0.001]). CONCLUSION: Evaluation of dose dependency showed that different concentrations of antioxidant NPs affect RBC. This effect can be changed oxidative stress and apoptosis. Using both changes to evaluate functional and toxicity can be helpful.